Implementation of 5S practices at 3K elite schools in Terengganu / Wan Asri Wan Ab Aziz, Nurlidaini Jaafar and Azman Che Mat - Wan Ab Aziz, Wan Asri; Jaafar, Nurlidaini; Che Mat, Azman (2015)
Nowadays, the Japanese 5S practices are often prevail among community organizations to enhance the capabilities and productivity. The study focused on the best management of teachers, students and its facilities through the process of 5's, a Japanese technology used in housekeeping index in improving the productivity of the school. This study effort dealt with the implementation of 5S methodology at secondary schools in Kemaman, Terengganu. By following the 5S methodology, this research effort may show significant improvements to safety, productivity, efficiency, and housekeeping. The study documented improvements by using before and after pictures. It also intends to build a stronger work ethic within the teachers and students who would be expected to continue the good practices. It is a movement to make sure that all the elements if a "workplace systems" function in order to allow the facilities to deliver an optimum level of performance. This study will use the technology of 5's to identify the effectiveness and standardize the operating systems in a systematic order adding more value to the schools.